Microvessel density, p53 overexpression, and apoptosis in invasive breast carcinoma. Issue 6 (December 1997) - Gonzalez-Palacios, F; Sancho, M; Martinez, J C; Bellas, C
Abstract : AIM: To investigate the possibility of a correlation among microvessel density, p53 overexpression, and apoptosis in invasive breast carcinoma. METHODS: Microvessel density was analysed in 105 cases of invasive breast carcinoma by immunohistology using antifactor VIII related antibody. The results were correlated with the immunohistochemical expression of p53 and the apoptotic index, detected using the in situ end labelling of fragmented DNA method (TUNEL). Assessment was made with a CAS 200 image analyser. All these studies were performed on formalin fixed, paraffin wax embedded tissue sections of tumour samples. RESULTS: The mean (SD) microvessel count was 47.2 (51.1), with a range from 7 to 250. Thirty five (33%) carcinomas showed overexpression of p53 protein. The apoptotic index of tumours ranged from 0.0 to 28.0, with a mean (SD) of 1.7 (3.2). The results showed that there was a significant inverse correlation between microvessel density and p53 expression (p = 0.04; odds ratio, 0.37). In contrast, no correlation was identified between the microvessel density and apoptotic index. CONCLUSIONS: These results suggest that in invasive breast carcinoma the p53 overexpression phenotype downregulates tumour neoangiogenesis, as does the wild-type of p53 protein. In addition, they suggest that apoptosis and neoangiogenesis in these tumours are independent processes.